1998
DOI: 10.1159/000030038
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoperative Serum Carcinoembryonic Antigen, CA 19-9 and Alpha Fetoprotein Levels in Gastric Cancer Patients

Abstract: The relationship between preoperative serum carcinoembryonic antigen (CEA), CA 19-9 and α-fetoprotein (AFP) levels and their clinicopathological features were evaluated in gastric cancer patients. The positive rates of CEA, CA 19-9 and AFP were 24.8, 27.6 and 12.7%, respectively. Gastric cancer with deeper tumor invasion was significantly more common among patients positive for these tumor markers. Patients with positive CEA or CA 19-9 values had a significantly high risk of lymph node metastases (p = 0.045 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
3
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 11 publications
2
38
3
1
Order By: Relevance
“…However, the preoperative serum CEA level has been reported to function as a useful marker for the prognosis of these tumors [3,4]. The positivity rate of CEA in our study was 15.9%, which is lower than the data reported by other investigators [8][9][10][11]. The positivity rate of CA 19-9 was 32.9%, which is also lower than in other studies [9,10].…”
Section: Discussioncontrasting
confidence: 78%
“…However, the preoperative serum CEA level has been reported to function as a useful marker for the prognosis of these tumors [3,4]. The positivity rate of CEA in our study was 15.9%, which is lower than the data reported by other investigators [8][9][10][11]. The positivity rate of CA 19-9 was 32.9%, which is also lower than in other studies [9,10].…”
Section: Discussioncontrasting
confidence: 78%
“…However, the related literature describes some different observations. Nakajima et al 17 reported that there was no correlation between preoperative afp values and histopathology, lymph node metastasis, vessel invasion, and liver metastasis. Lymph node involvement has been reported to be present in 62.9%-100% patients with afpgc 11-15 .…”
Section: Discussionmentioning
confidence: 99%
“…A few serum markers were found to be associated with poor prognosis in patients with gastric cancer and are therefore useful for monitoring and predicting early recurrence and poor prognosis [1,2]. The host infl ammatory response to cancer cells is also associated with tumor progression [3,4].…”
Section: Introductionmentioning
confidence: 99%